We know that inversion interchanges lines and circles, but it's very hard to

The inversion map about the unit circle is just $\displaystyle z \mapsto \frac{1}{\overline{z}}$. As a Möbius transformation maps circles to circles, let's try a circle with radius $1$ centered on the line $\mathrm{Re}(z)=3$:

$$ \big\{ z(t)= (3 + is) + e^{it} : 0 \leq t \leq 2 \pi \big\}$$

The image equation is easy write down, but to recognize but hard to identify as a circle:

$$ \frac{1}{(3-is)+e^{-it}}$$

What is the radius? Or the center? If $s = 0$ I thought I could make some headway. It is just as bad:

$$ \frac{1}{3+e^{-it}} = \frac{3 + e^{it}}{10 + 6\cos t}$$

Assuming the image is a circle, we can just notice that $2 \mapsto 1/2$ and $4 \mapsto 1/4$ so the new diameter is $\frac{1}{2}-\frac{1}{4} = \frac{1}{4}$ with the center at $( \frac{3}{8} ,0)$.

In the case of the line, a circle of radius $r = \infty$, it is possible to show by reparamerization that $z = 3 + it$ maps to the circle of radius $\frac{1}{3}$ and center $(0, \frac{1}{6}) $. I don't know how to do that in this case.


The given circle can be written as $|z-\alpha|=1$, where $\alpha=3+is$. The image points $w$ satisfy $$\Bigl|\frac1w-\alpha\Bigr|=1$$ which can be written $$|1-\alpha w|=|w|\ .$$ Now square both sides and write in terms of conjugates: $$\def\c#1{\overline{#1}}1-\alpha w-\c\alpha\c w+\alpha\c\alpha w\c w=w\c w\ .$$ Collecting terms and dividing by $\alpha\c\alpha-1$ (which is not zero) gives $$w\c w-\frac\alpha{\alpha\c\alpha-1}w-\frac{\c\alpha}{\alpha\c\alpha-1}\c w+\frac1{\alpha\c\alpha-1}=0$$ and hence $$\Bigl(w-\frac{\c\alpha}{\alpha\c\alpha-1}\Bigr) \Bigl(\c w-\frac\alpha{\alpha\c\alpha-1}\Bigr)=\langle\hbox{something}\rangle\ .$$ See if you can supply the missing RHS and finish the problem.


To complement David's nice algebraic derivation, notice to invert $|z - a| = 1$ about the unit circle, we can rotate the plane by phase $a/|a|$ so the center lies on the real axis.

enter image description here

The radius and center are just the average and difference in this case:

  • $$r = \frac{1}{2} \left( \frac{1}{|a|-1} - \frac{1}{|a|+1}\right) = \frac{1}{|a|^2 - 1}$$

  • $$z_0 = \frac{1}{2} \left( \frac{1}{|a|-1} + \frac{1}{|a|+1}\right) = \frac{|a|}{|a|^2 - 1}$$

For a general circle we will have $a$ instead of $|a|$ in the numerator.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.